Pengaruh Kinerja Keuangan Terhadap Nilai Perusahaan Sektor Makanan dan Minuman - Putri, Mifta Wardhani (Universitas Multi Data Palembang, 2025)
Research was conducted to evaluate the influence of financial performance, measured by Return on Assets (ROA) and Return on Equity (ROE), on company value in the food and beverage industry in the 2020-2023 period. Research data was obtained through annual reports of companies that met the criteria, with purposive sampling techniques used to select 76 samples over a period of four years. The data was processed using SPSS version 30 software. The research results explain that financial performance plays a significant role in determining company value in the food and beverage sector, with ROA as the main factor that has a significant impact.